2019
DOI: 10.3390/ma13010066
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Mechanical Properties and Impact-Induced Reaction Characteristics of PTFE/Al/CuO Reactive Materials

Abstract: Metal/fluoropolymer materials are typical reactive materials. Polytetrafluoroethylene (PTFE)/Al/CuO reactive materials were studied in this research. Scanning electron microscopy (SEM), quasi-static compression, the Split Hopkinson pressure bar test, and the drop hammer test were used to study the mechanical properties and induced reaction characteristics of the reactive materials with different Al/CuO thermite contents and different particle sizes. SEM images of the samples demonstrate that the reactive mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…As suggested by the test results, the existence of Ni was conducive to increasing the strain-hardening modulus and compressive strength of the material. Zhou et al 15 carried out research on the mechanical property of Al/PTFE/CuO(copper oxide), which led to the finding that, the strength of the micro-sized PTFE/Al/CuO first increased and then decreased with an increase in the concentration of Al/CuO thermite. With ZrH 2 introduced into Al/PTFE, Zhang et al 16 drew a conclusion that the gradation of particle size between Al and ZrH 2 produced a more significant effect than particle size.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by the test results, the existence of Ni was conducive to increasing the strain-hardening modulus and compressive strength of the material. Zhou et al 15 carried out research on the mechanical property of Al/PTFE/CuO(copper oxide), which led to the finding that, the strength of the micro-sized PTFE/Al/CuO first increased and then decreased with an increase in the concentration of Al/CuO thermite. With ZrH 2 introduced into Al/PTFE, Zhang et al 16 drew a conclusion that the gradation of particle size between Al and ZrH 2 produced a more significant effect than particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team has also carried out a lot of work on PTFE-based reactive materials and has obtained some research results. Zhou [ 21 ] studied the mechanical properties and impact-induced reaction characteristics of PTFE/Al/CuO reactive materials through a quasi-static compression test, a dynamic SHPB test and a drop hammer impact test, and also considered the effects of particle size and component distribution ratio of each matrix. Ding [ 22 ] studied the impact energy release characteristics of PTFE/Al/CuO reactive materials with a self-designed energy release testing device, and the effects of particle size, the ratio of PTFE/Al and Al/CuO materials and sintering on the energy release ability of the reactive materials were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the addition of CuO powder adjusted the reactive material's density and promoted the chemical reaction between the components of the reactive material. Zhou [15] found that adding Al/CuO thermite materials or using nano-scale PTFE and Al materials can significantly improve the reactive material sensitivity in drop hammer tests. Ran [16] studied PTFE/Al with B, Si, and CuO, respectively, and found that PTFE/Al/Si can produce higher pressure, indicating that it has a more vital destructive ability.…”
Section: Introductionmentioning
confidence: 99%